2005
DOI: 10.1021/jo050261x
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of Substituted Piperidinones from α,β-Unsaturated Amides:  Formal Synthesis of Deplancheine, Tacamonine, and Paroxetine

Abstract: [reaction: see text] An intermolecular aza-double Michael reaction leading to functionalized piperidin-2-ones from simple starting materials has been developed. The method allows alpha,beta-unsaturated amides to be used as a synthon of the piperidine nucleus. In addition, the utility of this methodology is demonstrated by its application to a formal synthesis of the indolo[2,3-a]quinolizidine alkaloids, (+/-)-deplancheine, (+/-)-tacamonine, and the antidepressant paroxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…In 2005, Takasu et al reported a synthesis of racemic piperidines from a,b-unsaturated amides by an intermolecular aza-double Michael addition. 3 In the realm of organocatalysis, 4 Jorgensen and coworkers reported a Michael addition 5 of malonates to a,b-unsaturated aldehydes that could be used to obtain piperidines in only three steps in excellent yields and enantioselectivities. 6,7 In 2007, Rios and Córdova 8 reported a synthesis of pyrrolidines from 2-amidomalonates and a,b-unsaturated aldehydes, catalyzed by simple secondary amines with excellent enantioselectivities and yields.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Takasu et al reported a synthesis of racemic piperidines from a,b-unsaturated amides by an intermolecular aza-double Michael addition. 3 In the realm of organocatalysis, 4 Jorgensen and coworkers reported a Michael addition 5 of malonates to a,b-unsaturated aldehydes that could be used to obtain piperidines in only three steps in excellent yields and enantioselectivities. 6,7 In 2007, Rios and Córdova 8 reported a synthesis of pyrrolidines from 2-amidomalonates and a,b-unsaturated aldehydes, catalyzed by simple secondary amines with excellent enantioselectivities and yields.…”
Section: Introductionmentioning
confidence: 99%
“…This was then condensed with sesame in the next step of to obtain Nmethyl paroxetine, using the novel solvent sulpholane and polar solvents like DMSO, N-methyl pyrrolidone, dimethyl acetamide, 2-ethoxy ethanol or methanol. N-methyl paroxetine obtained by this method was far more superior in quality than obtained by using prior art methods [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and the overall yield was in the range of 80% to 85% with respect to the starting (-) carbinol.…”
Section: Brief Process Development Historymentioning
confidence: 99%
“…The minor cis isomer 26 could be epimerized to 25 by treatment with NaOMe. The trans isomer 25 was reduced with LiAlH 4 to afford the piperidine 27, which had been correlated with paroxetine (28). Thus the important antidepressant was prepared in short steps.…”
Section: Aza Double Michael Reactionmentioning
confidence: 99%
“…Thus the important antidepressant was prepared in short steps. 27,28) The double Michael reaction was further applied to the syntheses of pentalenene (29), 29) pentalenic acid (30), 30) deoxypentalenic acid (31), 29) longiborneol (32), 15,31) cedrandiol (33), 32) 8,14-cedranoxide (34), 33) atisirene (35), 34,35) atisine (36), [36][37][38] estrane (37), 39) epilupinine (38), 40) and tacamonine (39) 41) (Fig. 1).…”
Section: Aza Double Michael Reactionmentioning
confidence: 99%